Istikhdām Al-Mutalāzimāt Al-Lafdziyyah fi Al-Ta - Nabila BOUCHARIF; Fella BELMEHDI (Universitas Islam Negeri Palangka Raya, 2020)
Collocations usage among translation master students in the University of Algiers II seems rather irregular when it comes to the transfer of English into Arabic. This paper examines the extent and causes of this irregularity through a descriptive field study conducted among students